PARADIGMA PENDIDIKAN BERBASIS MASYARAKAT (COMMUNITY BASED EDUCATION) - Syakdiah, Halimatun (Fakultas Agama Islam, 2019)
All educational activities that are currently developing basically have a goal of involving all components of education including the community. However, in reality the community lacks a proper place as a subject that plays an important role in every education policy. What's more, many people are used as objects and tools to reap profits. In fact, the contribution of the community is so clear and tangible in supporting efforts towards overall educational goals. On that basis, it is necessary to develop an education paradigm based on the community. an Education Paradigm that will reunite formal educational institutions with informal real-life communities. Thus formal and informal education is not just a story, but a complete reality. Thus, a learning society will be created.